Quantitative analysis based on atomic force microscopy characterization of interfacial properties between carbon fibers and epoxy resin subjected to hygrothermal and thermal treatments. (29th September 2020) - Yang, Chongchong; Zhu, Dandan; Yang, Futing; Liu, Qianli; Sun, Chengyuan; Lei, Kun; Zheng, Zhen; Wang, Xinling
Abstract: It has been proved the interface between fibers and resin matrix suffers from severe service conditions, but it was rarely explored how to directly and quantitatively evaluate those negative effects. In this work, a novelly-designed quantitative analysis method was established via atomic force microscopy (AFM) based on shrinkage degree of resin matrix, and was further applied to assess the effects of hygrothermal and thermal treatment on the interfacial adhesion property of carbon fibers/epoxy composites (CFRPs). This method presented that the shrinkage extent of resin around carbon fibers after treatment could in a certain extent reflect the interfacial properties at the stability and linear constraint region. Furthermore, interlaminar shear strength and interfacial shear strength measurements demonstrated the validity of this novel method for interfacial properties, and revealed that the interface was more susceptible to hygrothermal than thermal treatment. This method is believed promising for studies on the interface of fibers/resin composites. Graphical abstract: A novelly-designed quantitative analysis method was established via atomic force microscopy (AFM) based on shrinkage degree of resin matrix, and was further applied to assess the effects of hygrothermal and thermal treatment on the interfacial adhesion property of CFRPs. This method presented that the shrinkage extent of resin around carbon fibers after treatment could in a certain extent reflect the interfacial properties at the stability and linear constraint region. A large shrinkage of resin matrix meant poor interfacial adhesion in CFRPs. Image 1